Deprotonation of 1,2-dialkylpyridinium ions: a DFT study of reactivity and site selectivity - Gupta, Neelima; Garg, Reena; Shah, Kirti Kr.; Tanwar, Akhilesh; Pal, Sourav (Journal of Physical Chemistry A, 2007)
A site-selectivity model, based on the Fukui function as a local reactivity descriptor, has been applied to 1.2-disubstituted pyridinium ions incorporating two competing sites of similar reactivity, i.e., 1-methylene and 2-methylene, which may undergo deprotonation depending on the nature of substituent present on these moieties. Applicability of the local HSAB rule, in context with the Li-Evans' generalized HSAB principle suggesting the hard-hard interactions to be controlled by minimum Fukui function, has been illustrated. Global and local reactivity descriptors have been computed by carrying out DFT calculations at B3LYP/6-31++G** level using Mulliken and NPA methods for charge analysis. A comparison with the calculated deprotonation energies involving two sites indicates that the observed site selectivity in differently substituted pyridinium ions is better explained by the Li-Evans rule of minimum Fukui function for hard-hard interactions.